Cryptocurrency And Financial Inclusion: Bridging The Gap In Emerging Countries - Antonius Ary Setyawan; Hugo Prasetyo Winotoatmojo; Natasha Kristi Puspa Ananda (Dinasti Publisher, 2024)
The main purpose of this research is to determine the function of cryptocurrencies as a transactions medium in developing country and solve critical economic problems through the application of practical and ethical solutions from cryptocurrencies. The research objectives included examining the extent to which the adoption of cryptocurrency has disrupted traditional financial systems and affected economic development, as well as investigating the potential benefits and challenges of using cryptocurrency for emerging market. The results showed that cryptocurrency offers benefits such as reduced transaction costs, faster settlement times, and increased transparency in transactions. However, there are also challenges such as regulatory and legal hurdles, security concerns, and limited understanding of cryptocurrency. The study also highlights the factors that influence the adoption of cryptocurrency in international trade, including regulatory and legal frameworks, security concerns, awareness and understanding of cryptocurrency, transaction costs, and integration with existing systems. Overall, the study provides insights into the potential opportunities and challenges presented by cryptocurrency in global trade and commerce, and the implications for policymakers, businesses, and investors.